Empirical assessment of the impact on trade of product specific preferential rules of origin - Verdeja, Luis F. (2012)
This thesis addresses the issue of rules of origin and their impact on trade flows. Four objectives are sought: i) to provide further evidence on the impact on trade of product-specific preferential rules of origin; ii) to develop a restrictiveness index based on empirical findings; iii) to open the path for the impact of the rules of origin on particular sectors other than textiles; and iv) to contribute with further evidence on regime-wide provisions.